The Consumption-Based Capital Asset Pricing Model - Duffie, Darrell; Zame, William (Econometrica, 1989)
The paper provides conditions on the primitives of a continuous-time economy under which there exist equilibria obeying the Consumption-Based Capital Asset Pricing Model (CCAPM). The paper also extends the equilibrium characterization of interest rates of Cox, Ingersoll, and Ross (1985) to multi-agent economies. We do not use a Markovian state assumption.